1982
DOI: 10.1002/nau.1930010214
|View full text |Cite
|
Sign up to set email alerts
|

The development of reflex bladder activity following spinal cord injury in cats and a method to control it

Abstract: Spinal cord transection is associated with the development of detrusor external sphincter dyssynergia in cats. These findings indicate that the cat is a suitable model for the study of lower urinary tract dysfunction after spinal cord injury. Inhibition of reflex detrusor activity was achieved by activation of a sacral inhibitory pathway by electrical stimulation of the sacral roots or anal sphincter in normal and spinal-injured animals, indicating presence of a sacral inhibitory pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 9 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Phasic bursting EUS EMG activity has also been seen in other animals, including dogs [ 139 , 187 ] and some nonhuman primates [ 206 , 207 ]. However, EUS EMG activity is silenced during micturition in humans, pigs [ 31 ] and felines [ 208 , 209 , 210 ]; therefore, intravesical pressure oscillations with concomitant urethral sphincter activation indicates the presence of DSD after SCI. The fact that this potentially pathologic pattern of bladder and EUS activation in humans is a feature of normal voiding in mice, rats, dogs and NHPs complicates the use of these animal models for studying DSD; nonetheless, since the pattern of EUS EMG activation in DSD is significantly different from that of phasic bursting during voiding, it remains viable to use rodents for neurogenic bladder investigations with this understanding.…”
Section: Considerations For the Application Of Animal Models In Nlutd...mentioning
confidence: 99%
“…Phasic bursting EUS EMG activity has also been seen in other animals, including dogs [ 139 , 187 ] and some nonhuman primates [ 206 , 207 ]. However, EUS EMG activity is silenced during micturition in humans, pigs [ 31 ] and felines [ 208 , 209 , 210 ]; therefore, intravesical pressure oscillations with concomitant urethral sphincter activation indicates the presence of DSD after SCI. The fact that this potentially pathologic pattern of bladder and EUS activation in humans is a feature of normal voiding in mice, rats, dogs and NHPs complicates the use of these animal models for studying DSD; nonetheless, since the pattern of EUS EMG activation in DSD is significantly different from that of phasic bursting during voiding, it remains viable to use rodents for neurogenic bladder investigations with this understanding.…”
Section: Considerations For the Application Of Animal Models In Nlutd...mentioning
confidence: 99%
“…Vesical hypertonicity following lower-motor neuron lesions has traditionally been explained by detrusor supersensitivity to cholinergic agonists [Lapides, 1962;El-Salmy et al, 19851 and/or detrusor hypertrophy in the face of a fixed urethral closure pressure [McGuire et al, 1981;McGuire and Morrissey, 1982;McGuire, 19861. Our observations in the present study suggest that yet another factor may contribute to the development of hypertonicity in the lower-motor neurogenic bladder. It has been reported that postdecentralization adrenergic hyperinnervation of the detrusor is accompanied by exaggerated a-adrenergic responses; this was suggested as a factor in the development of hypertonicity in the decentralized bladder [Sundin and Dahlstrom, 1973;Sundin et al, 19771.…”
Section: Clinicomorphologic Correlationmentioning
confidence: 99%